2006
DOI: 10.1523/jneurosci.4182-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

ARF6 and EFA6A Regulate the Development and Maintenance of Dendritic Spines

Abstract: The cellular and molecular mechanisms underlying the development and maintenance of dendritic spines are not fully understood. ADP-ribosylation factor 6 (ARF6) is a small GTPase known to regulate actin remodeling and membrane traffic. Here, we report involvement of ARF6 and exchange factor for ARF6 (EFA6A) in the regulation of spine development and maintenance. An active form of ARF6 promotes the formation of dendritic spines at the expense of filopodia. EFA6A promotes spine formation in an ARF6 activation-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
122
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(132 citation statements)
references
References 50 publications
10
122
0
Order By: Relevance
“…18 As suggested by the presence of a PDZ-binding motif, the IQSEC2 protein is anchored at PSD via its interaction with PSD-95, which also interacts with NMDA receptors. 19,20 At the PSD, the IQSEC2 protein activates the ARF6 substrate that has been shown to regulate the formation and maintenance of dendritic spines, 21 the branching of axons and dendrites, 22,23 exocytosis and endocytosis of synaptic vesicles, 24,25 and receptor internalization. 25,26 Disease-related variants directly modify the DNA sequence or can influence mRNA splicing leading to the lack of the correct gene product or to the formation of truncated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…18 As suggested by the presence of a PDZ-binding motif, the IQSEC2 protein is anchored at PSD via its interaction with PSD-95, which also interacts with NMDA receptors. 19,20 At the PSD, the IQSEC2 protein activates the ARF6 substrate that has been shown to regulate the formation and maintenance of dendritic spines, 21 the branching of axons and dendrites, 22,23 exocytosis and endocytosis of synaptic vesicles, 24,25 and receptor internalization. 25,26 Disease-related variants directly modify the DNA sequence or can influence mRNA splicing leading to the lack of the correct gene product or to the formation of truncated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A further study to determine the role MMP-9 plays in chronic hypoperfusion would be to induce this damage model in MMP-9 knockout mice. IQSEC1(mRNA) and subsequent Arf6 (protein) are highly expressed in the brain [65]. This molecule is involved in actin dynamics, lipid modification and membrane trafficking, specifically axonal transport after damage [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of shRNAs was tested on protein levels of HA-tagged rat PAK1 or rat ARF6 in HEK293T cells (data not shown). Both PAK1 and ARF6 targeting sequences have been already reported (13,23). The fidelity of all constructs was verified by sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it was seen that ARF6 regulates early axonal and dendritic growth and branching (10,11). Besides its involvement in early neuronal morphogenesis, ARF6 is known to play a role in later stages of neuronal development, and recent studies have reported that ARF6 affects dendritic spine formation and causes morphological changes (11)(12)(13). These studies, however, presented contradictory results regarding the role of ARF6 in spine development.…”
mentioning
confidence: 99%
See 1 more Smart Citation